Validity and Reliability Studies of the Indonesian Version of the Minnesota Living with Heart Failure Questionnaire (MLHFQ): Quality of Life Questionnaire for Patients with Chronic Heart Failure - Dinas Yudha Kusuma; Hamzah Shatri; Idrus Alwi; Murdani Abdullah (Acta Medica Indonesiana, 2019)
Background: Minnesota Living with Heart Failure Questionnaire (MLHFQ) is the most commonly used questionnaire and it has a good EMPRO (Evaluating the Measurement of Patient-Reported Outcomes) score. The MLHFQ has been adapted and used by various countries worldwide. However, to be utilized in Indonesia, it needs validity and reliability studies. This study aimed to obtain a valid and reliable Indonesian version of the Minnesota Living with Heart Failure Questionnaire (MLHFQ) so that it can be used in Indonesia. Methods: the present study was a cross sectional study with 85 subjects (mean age 58 (SD 11) years; 55% subjects were male) who had chronic heart failure and was treated at the outpatient clinic of cardiology in Dr. Cipto Mangunkusumo Hospital, Jakarta. Validity of the MLHFQ was assessed by evaluating the construct validity using multitrait-multimethod analysis and external validity was evaluated by compairing  the MLHFQ with the SF-36 questionnaire.  Reliability was assessed using Cronbach’s α and intraclass correlation coefficients (ICC). Results: the Indonesian version of the MLHFQ had moderate-to-strong correlation between domains and items in questionnaire (r: 0.571-0.748; p<0.01) and it had moderate negative correlation with SF-36 questionnaire  (r -0.595; p<0.001). The Cronbach α of Indonesian version of MLHFQ was 0.887; while the ICCs was 0.918. Conclusion: the Indonesian version of MLHFQ has good validity and reliability to asses the quality of life of patients with chronic heart failure in Indonesia.